How to Make and Characterize Hydroxyapatite from Eggshell Using the Hydrothermal Method: Potential Insights for Drug Delivery System - Ferli Septi Irwansyah; Alfi Ikhlasul Amal; Eko Prabowo Hadisantoso; Atiek Rostika Noviyanti; Diana Rakhmawaty Eddy; Risdiana Risdiana; Suryana Suryana; Shariffuddin Bin Md Zain (Indonesian Journal of Science and Technology, 2023)
Hydroxyapatite (HA) has garnered significant attention as a versatile biomaterial with promising applications in drug delivery systems. This study aimed to synthesize and characterize HA derived from eggshells using the hydrothermal method and explore its potential insights for drug delivery systems. We delivered a step-by-step process to produce HA using a hydrothermal method, supported by several analyses, X-Ray Diffraction (XRD) to analyze the crystallinity structure, Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), Particle Size Analyzer (PSA), and Brunauer-Emmett-Teller (BET). The stage is continued with a study on the potential of HA as a drug delivery system with UV-Visible spectrophotometer instrumentation. The results suggest that the characterized HA suits drug delivery systems due to its favorable properties. This study contributes to the understanding of utilizing hydroxyapatite from eggshells as a viable material for drug delivery systems, opening avenues for further research and development in this field.